2013
DOI: 10.5455/musbed.20131204095705
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between a Primary School Fourth, Fifth, Sixth Grade Students' Aggressiveness Levels Parent Attitudes and Some Variables

Abstract: Bir ilköğretim okulu 4, 5, ve 6. Sınıf öğrencilerinin saldırganlık düzeylerinin anne baba tutumları ve bazı değişkenler ile ilişkisi Amaç: Bu çalışma ilköğretim öğrencilerinin saldırganlık düzeylerinin anne-baba tutumları ve bazı değişkenler ile ilişkisini belirlemek amacıyla yapıldı. Yöntem: Tanımlayıcı ve ilişki arayıcı tipteki bu çalışma Nisan-Mayıs 2011 tarihleri arasında bir ilköğretim okulunun dört, beş ve altıncı sınıf öğrencileri ile yürütüldü. Araştırmada örneklem seçimine gidilmeyerek dört, beş ve al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…14 Additionally, in some studies conducted in our country and abroad, aggression behaviors were found to be higher in males. 29,32,30,4,33,16,10 This result may be related to the acceptance or support of aggressive behaviors when male children are raised. In addition, by society, the girl's aggression and anger behaviours are expected that do not reveal and suppress and mens aggression behaviors are perceived as signs of power and masculinity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Additionally, in some studies conducted in our country and abroad, aggression behaviors were found to be higher in males. 29,32,30,4,33,16,10 This result may be related to the acceptance or support of aggressive behaviors when male children are raised. In addition, by society, the girl's aggression and anger behaviours are expected that do not reveal and suppress and mens aggression behaviors are perceived as signs of power and masculinity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found out that a lot of factor like family attitude, age, gender, academic success affects aggression at the children of secondary school. 8,14,15,16 It is seen that the aggression and violence incidents in our country and in the world are increasing day by day and spread in schools. 17 Aggression and violence in schools can take different forms like that a student's swearing to a person (such as student, teacher, administrator), physical damage and verbal threat, push at school corridor, fighting, threaten another person with a gun, taking drugs/alcohol, injuring and killing.…”
Section: Introductionmentioning
confidence: 99%